Appropriate Drying And Storage Conditions Of Hempedu Bumi (Andrographis Paniculata Nees) - Chong, Gun Hean (2002)
In this study, the forced air thin layer dryer was used for determining the appropriate drying condition of Andrographis paniculata. The quality of dehydrated A.paniculata was evaluated with andrographolide as reference compound. High performance liquid chromatography was used for the determination of andrographolide contained in A.paniculata. A suitable storage condition for preserving andrographolide in ground dried A.paniculata was also determined over a three-month storage study period. Three drying temperatures (55, 65 and 75°C) and air velocities (1.0, 1.5 and 2.0m/s) were utilized for the drying experiment with the observed air relative humidity of 66-80%. Drying temperature was found to be an important parameter affecting the drying time and the quality of A.paniculata. The andrographolide content was reduced by 37.54, 53.59 and 62.72% from the initial amount (17.5 ± 3.4 % wt/dry wt) for the drying temperatures of 55, 65 and 75°C, respectively. However, from the heating cost point of view, 75°C temperature and 1.0m/s air velocity was the appropriate drying condition for A.paniculata. since the cost per unit andrographolide remaining for that drying temperature was the lowest. On the other hand. a larger amount of andrographolide can be maintained with drying condition of 55°C drying temperature and 1.0m/s air velocity. Andrographolide was satisfactorily maintained at three selected storage conditions (5±2°C; 25±2°C with 60±5% RH; 30±2°C with 60±5%RH), which A.paniculata was kept in air tight glass bottle; without any significant reduction of this compound after three months. Therefore, ambient condition (30 ±2°C, 60±5% RH) is acceptable for storage of A.paniculata with respect to andrographolide preservation.